Arctic lakes are continuous methane sources to the atmosphere under warming conditions - Zeli Tan; Qianlai Zhuang (Environmental Research Letters, 2015)
Methane is the second most powerful carbon-based greenhouse gas in the atmosphere and its production in the natural environment through methanogenesis is positively correlated with temperature. Recent field studies showed that methane emissions from Arctic thermokarst lakes are significant and could increase by two- to four-fold due to global warming. But the estimates of this source are still poorly constrained. By using a process-based climate-sensitive lake biogeochemical model, we estimated that the total amount of methane emissions from Arctic lakes is 11.86 Tg yr ^−1 , which is in the range of recent estimates of 7.1–17.3 Tg yr ^−1 and is on the same order of methane emissions from northern high-latitude wetlands. The methane emission rate varies spatially over high latitudes from 110.8 mg CH _4 m ^−2 day ^−1 in Alaska to 12.7 mg CH _4 m ^−2 day ^−1 in northern Europe. Under Representative Concentration Pathways (RCP) 2.6 and 8.5 future climate scenarios, methane emissions from Arctic lakes will increase by 10.3 and 16.2 Tg CH _4 yr ^−1 , respectively, by the end of the 21st century.